Acute effects of two HIIT protocols on oxidative responses - George Franklin Santana de Carvalho; Anderson Carlos Marçal; Felipe José Aidar; Jymmys Lopes Santos; Ciro José Brito; Márcio Getirana-Mota; Clésio Andrade Lima; Ricardo Aurélio Carvalho Sampaio; Raphael Fabrício de Souza; Lucio Marques Vieira-Souza (Motricidade, 2022)
The aim of this experimental study was to evaluate acute responses to oxidative stress (OS) after a single session of two HIIT protocols. 24 Wistar rats were divided into three groups (n= 8): sedentary control (SC), HIIT with a 7-minute volume (LW) and HIIT with 14-min (HW). After the protocol, blood was collected for the measurement of uric acid (UA), and the liver and the gastrocnemius muscle were collected for OS assessment by measuring malondialdehyde (MDA) and total antioxidant capacity (FRAP). The LW and HW groups showed a reduction in hepatic MDA (51.9 and 29.9%; p< 0.05) compared to SC. However, the muscle of the HW group increased the MDA (12.6%; p< 0.05) compared to SC. As for FRAP, LW and HW reduced values (78.3 and 75.3%; p< 0.05, respectively) compared to SC. UA in the LW group was higher when compared to SC (64.7%; p< 0.05), HW group was similar to SC (p> 0.05). Among the different HIIT protocols, the LW group showed an increase in UA compared to the HW group (44%; p< 0.05). Compared to SC, the LW and HW groups did not promote acute OS in the liver tissue. However, HW caused OS in muscle tissue after a single exercise session.